PENGEMBANGAN DAYA TARIK LUTUNG JAWA (Trachypithecus auratus) SEBAGAI OBYEK WISATA SATWA LIAR DI TAMAN WISATA ALAM KAWAH IJEN-JAWA TIMUR - , Ali Purwanto ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Besides the volcanic crater, Kawah Ijen Nature Tourism Park has another attractive natural tourism object. It is the existence of javan langur (Trachypithecus auratus) in their natural habitat. However, information about the best location and time to observe javan langur was not available. Moreover, data about the perception of local community and tourist on the development of Javan Langur as tourist object was also not at hand. This research aimed to investigate the proper location and time for observation of javan langur as wildlife tourism object, to obtain tourists, local community, relevant governmental institution and natural tourism entrepreneur perceptions about javan langur as wildlife tourism object, and to establish development strategy of javan langur attraction. Research methods used were survey and interview. Location and observation time of javan langur data were collected by direct observation technique. Perception data were collected by questionary and interview technique. The collected data were processed and analyzed descriptively. The strategy for development of javan langur attraction as wildlife tourism object in Kawah Ijen Nature Tourism Park was built by using SWOT analysis. Research results showed that best location and time for javan langur observation as wildlife tourism object were at hm pole 18 with observation time I, IV, III and II, and at hm pole 17 with observation time I and IV, at hm 19 with observation time I and IV, at hm pole 8 with observation time I and IV, at hm pole 10 with observation time I, at hm 11 with observation time III, at hm pole 12 observation time IV, at hm pole 4 observation time II, at hm pole 7 observation time II, at hm pole 9 observation time IV and at hm pole 16 observation time II. Perception about javan langur attraction as wildlife tourism object was very high for local tourist, international tourist, government institution, as wel as natural tourism entrepreneur with a value of 81%, 81,64%, 87,8% and 87,05%, respectively, and high for villager of Taman Sari (77%) and Sumber Rejo (76,9%). The strategy must be conducted for developing javan langur attraction as wildlife tourism object was SO strategy (strenghts-opportunities) which included, preserve area quality, maintain and increase the market, improve human resource quality and institutional, develop partnership/collaborative natural tourism management.